MODEL LOGIT KUMULATIF UNTUK RESPON ORDINAL - Raharjanti, Robiah Peni Raharjanti; Widiharih, Tatik (MATEMATIKA, 2005)
Logit cumulative model is used to discribe the relationship between a response variable and one or more explanatory variables which response variable is of ordinal scale. To estimate the parameters, use maximum likelihood method with Newton Raphson iteration. Testing for the significance of the coefficients is done to fit the model. Test for overall significance of the variables in the model is performed by likelihood ratio test and test on individual coefficient is done using Wald’s test